2018
DOI: 10.1186/s13033-018-0255-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence access to mental health services in South-Eastern Europe

Abstract: IntroductionAccess to mental health (MH) services is unequal worldwide and changes are required in this respect.ObjectivesOur aim was to identify the delay to the first psychiatry consult and to understand patients’ characteristics and perspectives on the factors that may influence the delay, among a sample of participants from three Southeastern European Countries.Materials and methodsThe WHO Pathway Encounter Form questionnaire was applied in 400 patients “new cases” and a questionnaire on the factors influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
0
21
1
1
Order By: Relevance
“…A large body of included studies (85%) has reported that fear of being stigmatized hindered people from seeking MH services(17, 18, 20, 23-25, 31, 33, 35, 37, 39, 42, 44, 45, 48-50, 52-54).B-1-2-Personal stigma/Shame: according to the findings of current review, self-stigma and embarrassment is the second attitudinal barrier to the utilization of MH services. Self-stigma is a feeling of shame that in many cases leads to reduction in utilization of MH services(18,20,44,48,50,(52)(53)(54).B-1-3-Concerns about the effectiveness of services: this study indicates that another frequent barrier to the utilization of MH services in LMICs is concern about the effectiveness of services. Patients who suppose that MH service would not help them are less likely to seek and utilize these services(18, 23- 25, 48, 49).…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…A large body of included studies (85%) has reported that fear of being stigmatized hindered people from seeking MH services(17, 18, 20, 23-25, 31, 33, 35, 37, 39, 42, 44, 45, 48-50, 52-54).B-1-2-Personal stigma/Shame: according to the findings of current review, self-stigma and embarrassment is the second attitudinal barrier to the utilization of MH services. Self-stigma is a feeling of shame that in many cases leads to reduction in utilization of MH services(18,20,44,48,50,(52)(53)(54).B-1-3-Concerns about the effectiveness of services: this study indicates that another frequent barrier to the utilization of MH services in LMICs is concern about the effectiveness of services. Patients who suppose that MH service would not help them are less likely to seek and utilize these services(18, 23- 25, 48, 49).…”
mentioning
confidence: 84%
“…B-2-3-Lack of family or social support: we found that shortage of support from others is a deterrent factor against utilization of MH services in some developing countries. Social support of patients with mental illness has different dimensions including financial, emotional, and physical supports(18,33,35,45,48,49,52,53).B-2-4-Time-related barriers: this study showed that challenges pertaining to time are another structural barrier to the utilization of MH services in LMICs. These challenges include waiting time barriers, difficulty taking time off work, and transportation time.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…It is necessary to recognize that these histories have impacted health and wellness today by influencing how research into mental health from the region is done and contextualized (i.e., almost exclusive investigation of post-war conditions and PTSD). In addition to the significant funding difficulties and out-of-pocket payments to treat somatic diseases (see demographic research section), there is a chance that mental health issues may be even more threatened to be ignored due to significant stigma surrounding these problems and a lack of current available resources and treatments (Tirintica et al, 2018). When taken together, these barriers to healthcare impose a great risk to the overall mental wellbeing of Balkan peoples.…”
Section: Wars Of Yugoslav Successionmentioning
confidence: 99%